Analysis of Self Regulated Learning for Junior High School Students during the Online Learning Period - Mulyana Sapdi, Rohmat; Labib Abdillah, Zulfiyani; Sugilar, Hamdan (Gunung Djati Conference Series, 2022)
This study aims to determine the extent to which the level of self regulated learning mathematics in 8th grade junior high school students in online learning. The method used in this study is a descriptive method with a qualitative approach. The subjects studied in this study were 20 8th grade students of a SMPN in Cileunyi. The data collection technique used in this study is to provide a student self regulated learning questionnaire consisting of 10 statements that include 4 indicators. The data analysis technique used is the formula for the percentage of students' answers, then the interpretation criteria for the percentage of answers are used to describe the results of data analysis. Analysis of 20 students who answered the questionnaire revealed an average level of student independence in learning of 75%. Based on the results of these percentages, it can be interpreted that almost all students are able to learn mathematics independently, but considering the importance of student self regulated learning, it must be maintained and continuously improved